Prognostic Nomogram for Hepatitis B Virus–related Hepatocellular Carcinoma With Adjuvant Transarterial Chemoembolization After Radical Resection. (January 2020) - Huang, Jian; Liu, Fu-Chen; Li, Li; Yuan, Sheng-Xian; Yang, Yuan; Jiang, Bei-Ge; Liu, Hui; Pan, Ze-Ya
Abstract : Objectives: The objective of this study was to establish a reliable and effective nomogram for predicting prognosis of hepatitis B virus (HBV)–related hepatocellular carcinoma (HCC) with postoperative adjuvant transarterial chemoembolization (TACE). Patients and Methods: A derivation cohort of 370 HCC patients treated with postoperative TACE in the Eastern Hepatobiliary Surgery Hospital from January 2009 to December 2012 were retrospectively analyzed. Univariate and multivariate analysis were performed by Cox regression and independent prognostic factors for overall survival were determined to construct the nomogram. Concordance index (C-index), calibration curve and decision curve analysis were performed to evaluate the capability of the nomogram and the established nomogram was compared with TNM stage and Barcelona Clinic Liver Cancer (BCLC) stage to identify the superior model. The results were validated in a validation cohort of 123 HCC patients in the same center. Results: Multivariate analysis indicated that γ-glutamyl transferase, α-fetoprotein, tumor number, tumor size, satellite lesions, microvascular invasion, and HBV-DNA were independent prognostic factors for overall survival in the derivation cohort, and all these factors were selected into the nomogram. The C-index was 0.755 for survival prediction of the nomogram, which was significantly higher than the TNM stage (0.636, P <0.001) and BCLC stage (0.594, P <0.001). A fair uniformity and a superior net benefit with wide range threshold probabilities were showed in the calibration curves and decision curve analysis. In the validation cohort, the C-index of the nomogram (0.785) also had a higher predictive accuracy than TNM stage (0.744, P =0.019) and BCLC stage (0.616, P <0.001). Conclusions: The nomogram with accurate and reasonable performance was proposed for predicting survival of HBV-related HCC with postoperative adjuvant TACE.